\section{Introduction} \definition{} Say we have a sequence $a_0, a_1, a_2, ...$. \par The \textit{generating function} of this sequence is defined as follows: \begin{equation*} A(x) = \sum_{n=0}^\infty a_nx^n = a_0 + a_1x + a_2x^2 + a_3x^3 + ... \end{equation*} Under some circumstances, this sum does not converge, and thus $A(x)$ is undefined. \par However, we can still manipulate this infinite sum to get useful results even if $A(x)$ diverges. \problem{} Let $A(x)$ be the generating function of the sequence $a_n$, \par and let $B(x)$ be the generating function of the sequence $b_n$. \par Find the sequences that correspond to the following generating functions: \begin{itemize}[itemsep=2mm] \item $cA(x)$ \item $xA(x)$ \item $A(x) + B(x)$ \item $A(x)B(x)$ \end{itemize} \begin{solution} \begin{itemize}[itemsep=2mm] \item $cA(x)$ corresponds to $ca_n$ \item $xA(x)$ corresponds to $0, a_0, a_1, ...$ \item $A(x) + B(x)$ corresponds to $a_n+b_n$ \item $A(x)B(x)$ is $a_0b_0 + (a_0b_1 + a_1b_0)x + (a_0b_2 + a_1b_1 + a_2b_0)x^2 + ...$ \par Which corresponds to $c_n = \sum_{k=0}^n a_kb_{n-k}$ \end{itemize} \end{solution} \vfill \pagebreak \problem{} Assuming $|x| < 1$, show that \begin{equation*} \frac{1}{1-x} = 1 + x + x^2 + x^3 + ... \end{equation*} \hint{use some clever algebra. What is $x \times (1 + x + x^2 + ...)$? } \begin{solution} Let $S = 1 + x + x^2 + ...$ \par Then, $xS = x + x^2 + x^3 + ...$ \par \vspace{2mm} So, $xS = S - 1$ \par and $1 = S - xS = S(1 - x)$ \par and $S = \frac{1}{1-x}$. \end{solution} \vfill \problem{} Let $A(x)$ be the generating function of the sequence $a_n$. \par Find the sequence that corresponds to the generating function $\frac{A(x)}{1-x}$ \begin{solution} \begin{align*} \frac{A(x)}{1-x} &=~ A(x)(1 + x + x^2 + ...) \\ &=~ (a_0 + a_1x + a_2x^2 + ...)(1 + x + x^2 + ...)\\ &=~ a_0 + (a_0 + a_1)x + (a_0 + a_1 + a_2)x^2 + ... \end{align*} Which corresponds to the sequence $c_n = \sum_{k=0}^n a_k$ \end{solution} \vfill \problem{} Find short expressions for the generating functions for the following sequences: \begin{itemize} \item $1, 0, 1, 0, ...$ \item $1, 2, 4, 8, 16, ...$ \item $1, 2, 3, 4, 5, ...$ \end{itemize} \begin{solution} \begin{itemize}[itemsep=2mm] \item $1, 0, 1, 0, ...$ corresponds to $1 + x^2 + x^4 + ...$. \par By \ref{xminusone}, this is $\frac{1}{1-x^2}$. \item $1, 2, 4, 8, 16, ...$ corresponds to $1 + 2x + (2x)^2 + ...$. \par By \ref{xminusone}, this is $\frac{1}{1-2x}$. \item $1, 2, 3, 4, 5, ...$ corresponds to $1 + 2x + 3x^2 + 4x^3 + ...$.\par This is equal to $(1 + x + x^2 + ...)^2$, and thus is $\left(\frac{1}{1-x}\right)^2$ \end{itemize} \end{solution} \vfill \pagebreak